Co-inheritance of compound heterozygous Hb constant spring and a single -α 3.7 gene deletion with heterozygous δβ thalassaemia: A diagnostic challenge - Azma R.Z.; Othman A.; Azman N.; Alauddin H.; Ithnin A.; Yusof N.; Razak N.F.; Sardi N.H.; Hussin N.H. (2024)
Indexed by Scopus